Expectations and challenges: the implementation of mobile devices in a Scottish primary school. Issue 1 (1st January 2017) - Cornelius, Sarah; Shanks, Rachel
Abstract : This article provides a case study of the implementation of iPod Touches on a one-to-one basis in a Scottish primary school. It focuses on teachers' expectations for the project and the realisation (or otherwise) of these expectations. Findings suggest that the iPods offered opportunities for resource provision, interactive learning and extension activities. Technical challenges impacted on what could be achieved and some expectations, including sharing of resources and pupil work, and use for assessment, were not fully realised. Teachers also reported that some expected issues were quickly overcome. The development of teacher confidence with the devices remained a challenge after 12 months and they continued to seek meaningful ways to implement devices in the classroom. This case study contributes to our understanding of the pedagogical impact of mobile devices in schools and highlights the ways in which they can quickly become a valued part of the classroom environment. It suggests that implementation may not necessarily be a linear process of moving from assimilation to accommodation, as suggested by Lebrun, but that both phases may take place concurrently.